Efficacy and safety of deep brain stimulation in mesencephalic locomotor region for motor function in patients with post-stroke hemiplegia: a study protocol for a multi-center double-blind crossover randomized controlled trial - Xu, Junpeng; Liu, Bin; Liu, Shuzhen; Feng, Zhebin; Zhang, Yanyang; Liu, Di; Chang, Qing; Yang, Haonan; Chen, Yuhan; Yu, Xinguang; Mao, Zhiqi (Frontiers in Neurology, 2024)
Background Deep brain stimulation (DBS) is a potential treatment for improving movement disorder. However, few large-sample studies can reveal its efficacy and safety. This study aims to initially explore the efficacy and safety of DBS in the mesencephalic locomotor region (MLR) on motor function in patients with post-stroke hemiplegia. Methods/design This multicenter, prospective, double-blind, randomized crossover clinical trial aims to assess the safety and effectiveness of Deep Brain Stimulation (DBS) in the mesencephalic locomotor region (MLR) for patients with moderate to severe post-stroke hemiplegia. Sixty-two patients with stable disease after a year of conservative treatment will be enrolled and implanted with deep brain electrodes. Post-surgery, patients will be randomly assigned to either the DBS group or the control group, with 31 patients in each. The DBS group will receive electrical stimulation 1 month later, while the control group will undergo sham stimulation. Stimulation will be discontinued after 3 and 6 months, followed by a 2-week washout period. Subsequently, the control group will receive electrical stimulation, while the DBS group will undergo sham stimulation. Both groups will resume electrical stimulation at the 9th and 12th-month follow-ups. Post-12-month follow-up, motor-related scores will be collected for analysis, with the Fugl-Meyer Assessment Upper Extremity Scale (FMA-UE) as the primary metric. Secondary outcomes include balance function, neuropsychiatric behavior, fall risk, daily living activities, and quality of life. This study aims to provide insights into the therapeutic benefits of DBS for post-stroke hemiplegia patients. Result/conclusion We proposed this study for the first time to comprehensively explore the effectiveness and safety of DBS in improving motor function for post-stroke hemiplegia, and provide evidence for DBS in the treatment of post-stroke hemiplegia. Study limitations are related to the small sample size and short study period. Clinical Trial Registration Clinicaltrials.gov, identifier NCT05968248.